The InVance® sling procedure for male stress urinary incontinence: InVance® sling postopek za zdravljenje moške stresne urinske inkontinence - Bratuš, Dejan; Hlebič, Gregor (Acta Medico-Biotechnica, 2021)
Purpose: In men, stress urinary incontinence is relatively uncommon and usually follows a major surgical procedure. Other causes (neurogenic) are rare. Although uncommon, it has a big impact on the quality-of-life of affected patients because it interferes with their daily activities and social life.Methods: One of the recently developed methods of treating this condition is the InVance¨ Male Sling system. The silicone-coated polyester mesh is anchored to the pubic bone and supports the urethra, pressing it against the pubic symphisis. We analyzed the mid-term results of this method.Results: Two urologists treated 38 patients with this method between 2004 and 2007. Thirty-four subjects had urinary incontinence after radical prostatectomy and 4 cases after transurethral resection of the prostate. All had mild-to-moderate day-time stress urinary incontinence. Patients were followed up for ³2 years. Twenty-eight of them were completely dry and did not use any pads for protection. Six patients had mild residual stress urinary retention and used one pad daily. Four patients remained incontinent with no improvement. No major early complications, urinary retentions or de-novo micturition problems (urgency) were reported after the procedure.Conclusions: The InVance Sling method is a simple way to treat male stress urinary incontinence and has good mid-term results. Larger studies are needed to confirm the safety of this method.
Keywords: Male urinary stress incontinence; sling procedure; treatment results; minimally invasive procedure; postoperative complications